FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Basith, Abdul; Agustina, Rismia; Diani, Noor (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
Anemia is a condition which is more common in adolescent girls, which can be caused by variousfactors such as nutritional status, menstruation, and socioeconomic. Anemia can cause a personto experience a decrease in the immune system and causes the body susceptible to healthproblems. The objective of this study was to determine the factors associated with the incidenceof anemia among adolescent girls in SMP Negeri 4 Banjarbaru. The study results show thatfactor associated with anemia are period of menstruation (p = 0.003), the length of the menstrualcycle (p = 0.004), education level of parents (mother) (p = 0.000), and the income level ofparents (p = 0.000) , The factor which is not associated with anemia is nutritional status (p =0.064). The period and length of abnormal menstrual cycle can cause anemia because bloodremoved will be more than the normal amount. Mother's education level and parents’ low incomewill lead to anemia due to lack ofchildren’s needs fulfillment.